2009
DOI: 10.1111/j.1399-302x.2009.00542.x
|View full text |Cite
|
Sign up to set email alerts
|

Detection of herpetic viruses in gingival crevicular fluid of patients suffering from periodontal diseases: prevalence and effect of treatment

Abstract: This study showed that the prevalence of HCMV and HSV viruses in GCF is higher in patients suffering from periodontitis compared to periodontally healthy subjects, and that the prevalence of HCMV is higher in deep periodontal pockets. It also brought evidences that periodontal therapy may be associated with virus elimination in diseased sites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
64
3
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(73 citation statements)
references
References 19 publications
4
64
3
2
Order By: Relevance
“…[12][13][14] . Infection by HCMV or EBV seems to inhibit the macrophages to respond to bacterial challenge, and thus have pathogenic role in the development of periodontal disease.…”
Section: Human Cytomegalovirus (Hcmv) Epstein-barr Virus (Ebv) and Hmentioning
confidence: 99%
“…[12][13][14] . Infection by HCMV or EBV seems to inhibit the macrophages to respond to bacterial challenge, and thus have pathogenic role in the development of periodontal disease.…”
Section: Human Cytomegalovirus (Hcmv) Epstein-barr Virus (Ebv) and Hmentioning
confidence: 99%
“…5 There has been conflicting evidence found in a few studies from around the globe which suggest that the EBV and the HCMV are present at fewer periodontal sites than considered otherwise. [6][7][8][9][10][11][12] Because of the paucity of data and studies with larger sample size in Indian subjects, the exact picture of the presence of the herpesvirus in this population is still unclear. This study was undertaken to determine…”
Section: Introductionmentioning
confidence: 99%
“…A larger number of studies have been conducted on patients with periodontitis. Grenier et al 17 evaluated the 28 . In the present study detection frequency for EBV and CMV observed in patients with periodontitis is consistent with previous reports, confirming their presence in patients with periodontal disease and deep periodontal pockets.…”
Section: Discussionmentioning
confidence: 99%
“…However, in the last decade the presence of herpesviruses has been shown, including HSV1 and 2, EBV, and CMV in periodontal pockets of patients with periodontitis [16][17][18][19][20][21][22] .…”
Section: Discussionmentioning
confidence: 99%